Кто оставил Льва Толстого в Петербурге? («Флигель-адъютантская» протекция в жизни и творчестве писателя) [“Who Left Leo Tolstoy in St. Petersburg? Aides-de-Champ and Their Protection in Leo Tolstoy’s Life and Works”] - Krasnoselskaia, Yulia (Slavica Revalensia, 2018)
The aim of this article is to find a most probable answer to the following question: due to whose aid was Leo Tolstoy allowed to stay in St. Petersburg in November 1855, i.e. during the Crimean War? It refutes several hypotheses, including that of Tolstoy himself, who in his later years attributed this decision to Nicholas I, and proposes two likely candidates for the role of Tolstoi’s patrons: aides-de-champ Dmitri Gorchakov (1828—1907) and Arkadi Stolypin (1821—1899). The article also explores the subject of patronage in Tolstoi’s major writings, including War and Peace.